Description of a new species, Setaleyrodes machili Dubey, sp. nov. (Hemiptera: Aleyrodidae) infesting Machilus odoratissima Nees (Lauraceae) in Western Himalaya, India - Dubey, Anil Kumar (Zootaxa, 2017)
A new species of whitefly, Setaleyrodes machili Dubey sp. nov. found infesting Machilus odoratissima Nees (Lauraceae) is described from Kufri in Himachal Pradesh and Dhanaulti and Nainital in Uttarakhand, India. The diagnostic characteristics of puparia and habitus, are illustrated with line drawings and scanning electron microphotographs. Sexual dimorphism and variation in pigmentation during the transformation of instars are noted. An identification key to puparia of Setaleyrodes species so far described is presented.